Low Carbon Concept of Sruni Village through The System of Renewable Energy - Erni Setyowati; Nashrullah Dahlan Lubis; Subrata Aditama Kittie Aidon Uda; Agitta Raras Putri (Journal of Architectural Design and Urbanism, 2018)
Indonesia is the fourth most populous country in the world. The highest population density exists in urban areas and gradually becomes lower in periphery or rural. Therefore the city in Indonesia often looks slum because of over density. The village is the smallest part of a city. In crowded cities there are often slum villages. This paper highlights a model of slum villages in Wonosobo, Sruni village, and solutions to transform socio-cultural communities through renewable energy design based on low carbon concept. The method used is quantitative method based on demographic data of Sruni village, Wonosobo. Based on data and analysis, it is found that renewable energy that can be applied in Sruni village are sanitation, drainage and water waste management, solid waste, rain water harvesting, water wheel and solar panel energy. At the end of the discussion, it is concluded that there are needs to be re-densification or verticalization of the house, in order to obtain more public green open spaces. Meanwhile, based on quantitative analysis, Sruni village needs rain water harvesting system, additional 1 unit of communal Sewage Treatment Plant (STP) serving 80-100 households gray and black water, and 1 units of water wheels to accomodate electricity need of four inhabitant RTs in Sruni village .